Multi metabolomics-based analysis of application of Astragalus membranaceus in the treatment of hyperuricemia - Zhang, Wenwen; Cui, Yifang; Zhang, Jiayu (Frontiers in Pharmacology, 2022)
Hyperuricemia (HUA) is a common metabolic disease that is an independent risk factor for comorbidities such as hypertension, chronic kidney disease, and coronary artery disease. The prevalence of HUA has increased over the last several decades with improved living standards and increased lifespans. Metabolites are considered the most direct reflection of individual physiological and pathological conditions, and represent attractive candidates to provide deep insights into disease phenotypes. Metabolomics, a technique used to profile metabolites in biofluids and tissues, is a powerful tool for identification of novel biomarkers, and can be used to provide valuable insights into the etiopathogenesis of metabolic diseases and to evaluate the efficacy of drugs. In this study, multi metabolomics-based analysis of the blood, urine, and feces of rats with HUA showed that HUA significantly altered metabolite profiles. Astragalus membranaceus (AM) and benbromomalone significantly mitigated these changes in blood and feces, but not in urine. Some crucial metabolic pathways including lipid metabolism, lipid signaling, hormones synthesis, unsaturated fatty acid (UFAs) absorption, and tryptophan metabolism, were seriously disrupted in HUA rats. In addition, AM administration exerted better treatment effects on HUA than benbromomalone. Furthermore, additional supplementation with UFAs and tryptophan may also induce therapeutic effects against HUA.